Vitreous hemorrhage in a pregnant woman with a history of simultaneous pancreas and kidney transplantation: A case report - Wajd Aljabri; Saeed Baradwan; Alyaa Alkaff (Elsevier, 2023)
Pregnancy after simultaneous pancreas and kidney transplantation (SPKT) carries a high risk of maternal and fetal complications. We report the case of a 39-year-old woman with three consecutive pregnancies with favorable outcomes after SPKT. Within the first year of SPKT, the patient had a spontaneous pregnancy. At 32 weeks of gestation, she underwent an emergency cesarean section (CS) due to severe preeclampsia and HELLP syndrome. The infant was of average birth weight and was transferred to the neonatal intensive care unit for further management. A second unplanned pregnancy occurred almost nine months after the first. The antenatal assessments for fetal growth, blood glucose, and blood pressure were normal throughout follow-up. Early in her pregnancy, the patient developed an uneventful retinopathy of the left eye. At 37 weeks of gestation, she underwent an elective CS due to a short inter-pregnancy interval and delivered a healthy baby with an average birth weight. At the age of 39 years, the patient had a third unplanned pregnancy. She was diagnosed with seronegative antiphospholipid syndrome. She suffered from bilateral vitreous hemorrhage and was managed successfully with a minimally invasive laser treatment combined with an intravitreal injection of anti-vascular endothelial growth factor during her third trimester. At 35 weeks of gestation, the patient presented with labor pain and underwent an emergency CS and delivered a healthy baby with an average birth weight. Pregnancy after SPKT requires a multidisciplinary approach with a careful workup.